Atsaru Kharithah Dzihniyah fi Ta'alum al Af'al (Dirasah Tajribiyah fi Madrasah al Khairiyah al Tsanawiyah al Islamiyah al Ahliyah Jakarta al Janubiyyah - Nasution, Nirwana sari; Rahmawati, Siti Uriana; Raswan, Raswan (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2025)
This research aims to determine the effect of using mind mapping on fi'il learning at MA Al-Khairiyah. It employs a quantitative approach with an experimental method using a one-group pretest-posttest design. The sample consists of 30 tenth-grade students from MA Al-Khairiyah. This design does not require a control and experimental class; instead, it involves a single class that undergoes a pretest, treatment, and posttest. Before the treatment, students were given 10 questions as a pretest. In the next session, learning was conducted using mind mapping, after which students' comprehension was assessed through a posttest. The posttest results were then compared to the pretest results to determine whether there was an improvement or decline. The data collection techniques used in this research include observation, interviews, and tests. The findings prove that fi'il learning using mind mapping has a significant effect, as evident in the improvement of students' learning outcomes. This is supported by the pretest score of 46.6 and the posttest score of 83.3. Furthermore, the t-test results show that the calculated t value (10.58) is greater than the critical t value (1.699), indicating that Hâ‚€ is rejected and Hâ‚ is accepted. Therefore, that mind mapping has a positive impact on fi'il learning